Wings - Pike, Aprilynne (Pike, Aprilynne. Laurel., 2010)
When a plant blooms out of fifteen-year-old Laurel's back, it leads her to discover the fact that she is a faerie and has a crucial role to play in keeping the world safe from encroaching enemy trolls.